Are shear force methods adequately reported?. (September 2016) - Holman, Benjamin W.B.; Fowler, Stephanie M.; Hopkins, David L.
Abstract: This study aimed to determine the detail to which shear force (SF) protocols and methods have been reported in the scientific literature between 2009 and 2015. Articles ( n  = 734) published in peer-reviewed animal and food science journals and limited to only those testing the SF of unprocessed and non-fabricated mammal meats were evaluated. It was found that most of these SF articles originated in Europe (35.3%), investigated bovine species (49.0%), measured m. longissimus samples (55.2%), used tenderometers manufactured by Instron (31.2%), and equipped with Warner–Bratzler blades (68.8%). SF samples were also predominantly thawed prior to cooking (37.1%) and cooked sous vide, using a water bath (50.5%). Information pertaining to blade crosshead speed (47.5%), recorded SF resistance (56.7%), muscle fibre orientation when tested (49.2%), sub-section or core dimension (21.8%), end-point temperature (29.3%), and other factors contributing to SF variation were often omitted. This base failure diminishes repeatability and accurate SF interpretation, and must therefore be rectified. Highlights: Meat studies insufficiently detail shear force methods applied. Different key factors driving shear force variability were frequently omitted. Interpretation and replication depend on reporting shear force accurately.